Characteristic of Lamb Sausages Fermented by Indonesian Meat-Derived Probiotic, Lactobacillus plantarum IIA-2C12 and Lactobacillus acidophilus IIA-2B4 - Noraimah Binti Sulaiman; Irma Isnafia Arief; Cahyo Budiman (Media Peternakan, 2016)
Probiotic is a group of microorganism, mainly from lactic acid bacteria (LAB), widely used to increase functionality of various foodstuffs, including lamb which was limited by its goaty odor and short life issue. This study aimed to evaluate the characteristic of lamb sausages fermented by either Lactobacillus plantarum IIA-2C12 or L. acidophilus IIA-2B4 isolated from local cattle in Indonesia, and stored for 21 days at low temperature (4oC). Fermented lamb sausages were made with the addition of L. plantarum IIA-2C12 and L. acidophilus IIA-2B4 with three replications. The result showed that pH value, protein, and cholesterol contents of the sausages with addition of L. acidophilus IIA-2B4 were higher (P<0.05) than that of L. plantarum IIA-2C12. Meanwhile, the sausage fermented with L. plantarum IIA-2C12 had higher titratable acid (TA) value, texture, and the content of fat, carbohydrate, tyrosine, lysine, myristoleic (C14:1), pentadecanoic (C15:0), heneicosanoic (C21:0) and cis-11-eicosatrienoic (C20:1) as compared to that of  L. acidophilus 2C12-2B4. Final population of LAB in the sausage fermented by L. plantarum IIA-2C12 was also higher than that of L. acidophilus IIA-2B4, yet both can be categorized as a probiotic. The differences between characteristics of the physicochemical traits and microbiological quality of the sausage fermentation associated with the addition of L. plantarum IIA-2C12 or L. acidophilus IIA-2B4. The 21 days of storage at cold temperatures with probiotics addition could extend shelf life and maintain quality of fermented sausage.